Pathway Colleges: A New Institutional Form in Canada - McCartney, Dale M.; Scott Metcalfe, Amy (International Higher Education, 2018)
Canada’s public universities seeking to increase their international student recruitment are building pathways that allow students who lack the academic or language credentials needed for direct entry to the university to upgrade their skills and eventually matriculate to the larger institution. These pathway colleges are a new institutional form in Canada, but as yet they have received almost no attention from scholars. This paper offers a brief typology of these emerging institutions and offers some suggestions for future research.